Effects of insularity on insect leaf herbivory and chemical defences in a Mediterranean oak species - Xoaquín Moreira; Bastien Castagneyrol; Raúl de la Mata; Nikolaos M. Fyllas; Andrea Galmán; Carlos García‐Verdugo; Asier R. Larrinaga; Luis Abdala‐Roberts (Journal of Biogeography, 2019)
Aim Research on plant–herbivore interactions has shown that islands typically have low abundances and diversity of herbivores because of barriers to dispersal, isolation and reduced land area. Islands commonly have lower levels of herbivory relative to mainland regions, and, as a consequence, insular plants should exhibit lower levels of defences than their mainland counterparts. Despite these predictions, there are significant gaps in our understanding of insularity effects on plant–herbivore interactions. For instance, most work addressing the effects of insularity on plant–herbivore interactions have compared one or a few islands with a single mainland site. In addition, studies have measured herbivory or plant defences but not both, and the influence of abiotic factors has been neglected. Location Mediterranean Basin (from Spain to Greece). Taxon Quercus ilex L. Methods We conducted a large‐scale study to investigate whether insect leaf herbivory and plant chemical defences in holm oak ( Quercus ilex L.) differ between insular versus mainland populations. We further investigated mechanisms by which insularity effects on herbivory may take place by assessing the influence of defences and climatic variables on herbivory. Results We found that insular populations exhibited lower herbivory and higher defences (condensed tannins) than their mainland counterparts. Our analyses, however, suggest that these concomitant patterns of insect herbivory and plant defences were seemingly unrelated as island versus mainland differences in defences did not account for the observed pattern in herbivory. Furthermore, climatic factors did not explain insularity effects on either herbivory or plant defences. Main conclusions Overall, this study provides one of the most robust assessments to date on insularity effects on herbivory and builds towards a better understanding of the ecology and evolution of plant–insect interactions in insular ecosystems.